Dimensionamento e implantação de um sistema Off-Grid em Cachoeirinha do Mentae - comunidade da resex Tapajós Arapiuns na Amazônia - LACERDA, Gabriel Yúri Campos (Universidade Federal do Oeste do Pará, 2024)
This article deals with the design and installation of an off-grid system in the community of Cachoeirinha do Mentae, located in the Tapajós-Arapiuns Extractive Reserve of the Amazon, having as main objective its dimensional detailing. The project also addresses the importance of installing photovoltaic systems that deal with a clean source of energy supply using solar radiation, a free and abundant resource, mainly in the northern region of the country, in isolated rural communities where, in addition to having a forest dense and vast hydrographic network that makes the use of conventional systems difficult, there are also socioenvironmental, technical and financial elements that enhance the project's implementation. Therefore, the system was developed to meet the demands of the consumer units chosen by the community, taking into account the collective use, the energy needs of the unit and the climatic seasonality, in order to provide an improvement in the quality of life of the residents. community, mainly in education, health and economy